Careers Library: Unconventional collaboration to boost learning - Usova, Tatiana (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2023)
The pressure on higher education institutions to produce employment-ready graduates is high, and academic libraries can contribute to this goal by collaborating with non-academic departments. The Georgetown University in Qatar library partnered with the Career Services Centre and the Alumni office in launching Careers Library programme that expanded on the idea of the Human Library by creating an online week-long event aimed at empowering senior students with the knowledge and skills necessary to succeed in professional life after graduation.This practice paper illustrates how the library can engage in broader activities beyond information literacy instruction and leverage alumni relationships to develop students’ competencies. The collaboration proved to be beneficial and it fits well within the framework of library outreach activities. The value to the academic community is that this event can be easily replicated and it offers an easy way to draw on the expertise of alumni willing to give back to their school.